The Reserve Base, Reserve Requirements, and the Equilibrium Rate of Interest: Comment - Meyer, Paul A. (Quarterly Journal of Economics, 1968)
Journal Article The Reserve Base, Reserve Requirements, and the Equilibrium Rate of Interest: Comment Get access Paul A. Meyer Paul A. Meyer University of Maryland Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 82, Issue 3, August 1968, Pages 498–504, https://doi.org/10.2307/1879520 Published: 01 August 1968